2007
DOI: 10.1109/tac.2007.902763
|View full text |Cite
|
Sign up to set email alerts
|

PID Stabilization of MIMO Plants

Abstract: Abstract-Closed-loop stabilization using proportional-integral-derivative (PID) controllers is investigated for linear multiple-input-multiple-output (MIMO) plants. General necessary conditions for existence of PID-controllers are derived. Several plant classes that admit PID-controllers are explicitly described. Plants with only one or two unstable zeros at or "close" to the origin (alternatively, at or close to infinity) as well as plants with only one or two unstable poles which are at or close to origin ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…What's more, as the lemma-2 mentioned in Gundes and Ozguler 17 if plant G can admit a subset of a PID controller where at least one of the three constants K p , K d , and K i is nonzero as in equation ( 2), then G can also admit a PID controller so that any two or all of the three constants are nonzero, where the integral constant K i can be nonzero only if G has no transmission zeros at s ¼ 0. As an extreme form of MIMO, the servo plant which is strongly stabilizable and has no transmission zeros at s ¼ 0, can admit the above lemma.…”
Section: Pid Parameter's Role In Control Processmentioning
confidence: 92%
See 2 more Smart Citations
“…What's more, as the lemma-2 mentioned in Gundes and Ozguler 17 if plant G can admit a subset of a PID controller where at least one of the three constants K p , K d , and K i is nonzero as in equation ( 2), then G can also admit a PID controller so that any two or all of the three constants are nonzero, where the integral constant K i can be nonzero only if G has no transmission zeros at s ¼ 0. As an extreme form of MIMO, the servo plant which is strongly stabilizable and has no transmission zeros at s ¼ 0, can admit the above lemma.…”
Section: Pid Parameter's Role In Control Processmentioning
confidence: 92%
“…Cubic equivalent using real coefficient can also be expressed using roots as (I) and (II) of equation (17).…”
Section: Feedback Gains Of Imposed Axesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Su et al [ 15 ] applied the method of Han proposed for controlling of manipulator successfully. Gundes and Ozguler [ 16 ] investigated the problem of closed-loop stabilization using PID controller for MIMO plants to show the existence of stabilizing PID controllers for MIMO plants. Alvarez-Ramirez et al [ 17 ] addressed the position regulation problem of robot manipulators under control input constraints and experiment results showed that the saturated linear PID control was semiglobally asymptotically stable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proportional integral derivative (PID) control is one of the most commonly used control methods in various fields. Since 1942, researchers have put forward many PID control methods [21,22]. However, the controlled object generally has great uncertainty or complex nonlinearity in practical applications.…”
Section: Introductionmentioning
confidence: 99%